Analysis of morphometric and haemodynamic indicators of cardiac function in high-performance handball players during the competitive season - Sherstyuk, S.A.; Sherstyuk, A.A. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to identify the dynamics of cardiac morphometric and haemodynamic parameters during the competitive period of the annual training cycle in an elite men’s handball team. Methods and structure of the study. The study involved 19 elite athletes competing in the main squad of a team regularly participating in the Russian Men’s Handball Superleague Championship (EG – experimental group). Athletes’ ages ranged from 18 to 32 years. Assessment of cardiac morphometric and haemodynamic parameters was conducted using echocardiography (ECHO-CG) as part of the Superleague team’s medical support. Diagnostic ultrasound equipment “Mindray Z60” was employed. Results and conclusions. The dynamics of cardiac morphometric and haemodynamic parameters in professional handball players during the annual competitive cycle remained stable with a tendency towards increased efficiency, characterising their readiness to tolerate training loads of various orientations. Correlation analysis in the quantitative assessment of cardiac structures and chambers should be taken into account in the individualisation of the training process and in monitoring athletes’ condition throughout the annual competitive cycle.